2012
DOI: 10.3389/fpsyg.2012.00083
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Social Identity in Ants

Abstract: Recognizing the identity of others, from the individual to the group level, is a hallmark of society. Ants, and other social insects, have evolved advanced societies characterized by efficient social recognition systems. Colony identity is mediated by colony specific signature mixtures, a blend of hydrocarbons present on the cuticle of every individual (the “label”). Recognition occurs when an ant encounters another individual, and compares the label it perceives to an internal representation of its own colony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
53
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 77 publications
(100 reference statements)
2
53
0
5
Order By: Relevance
“…It has already been proved that young ants early know their nest odor thanks to habituation and/or imprinting [15]. Working on the species Myrmica rubra (Linnaeus, 1758), we showed that young workers become imprinted to their nest entrance odor and learn thereafter, thanks to operant conditioning, the visual aspects of such entrances [16].…”
Section: Introductionmentioning
confidence: 98%
“…It has already been proved that young ants early know their nest odor thanks to habituation and/or imprinting [15]. Working on the species Myrmica rubra (Linnaeus, 1758), we showed that young workers become imprinted to their nest entrance odor and learn thereafter, thanks to operant conditioning, the visual aspects of such entrances [16].…”
Section: Introductionmentioning
confidence: 98%
“…Processing of chemical cues appears to be decentralized, requiring at its basic level, nothing more than habituation at the antennal lobe level-elementary type of behavioural plasticity mediated by neuro-modulation-or sensory adaptation [19]. Even if some form of long-term memory is involved, a wasp only has to memorize one odour or a pattern of molecules [19].…”
Section: Introductionmentioning
confidence: 99%
“…Processing of chemical cues appears to be decentralized, requiring at its basic level, nothing more than habituation at the antennal lobe level-elementary type of behavioural plasticity mediated by neuro-modulation-or sensory adaptation [19]. Even if some form of long-term memory is involved, a wasp only has to memorize one odour or a pattern of molecules [19]. Conversely, since there is no known single visual cue by which all members of a colony can be identified, visual recognition requires specific memories not just of one defining feature, but of all the individual faces of one's colony.…”
Section: Introductionmentioning
confidence: 99%
“…Reconhecer membros do mesmo grupo e de grupos estrangeiros, identificando familiares dependendo da relação genética, é fundamental para evolução do comportamento social, permitindo que comportamentos altruístas sejam direcionados para indivíduos com alto grau de parentesco . Dessa forma, o reconhecimento de companheiros de ninho é uma característica central para manutenção da coesão colonial em insetos sociais , já que permite não apenas o altruísmo para parentes, mas também, a defesa territorial e de recursos ambientais, proporcionando o reconhecimento de intrusos assim como evitando a ação de parasitas Crozier & Pamilo, 1996;Bos & D'Ettorre, 2012).…”
Section: Introductionunclassified
“…Existem várias evidências de que os hidrocarbonetos cuticulares têm participado como sinais olfativos durante o mecanismo de reconhecimento e discriminação de companheiros de ninho em formigas Carlin, 1989;Bos & D'Ettorre, 2012;.…”
Section: Introductionunclassified